Collaborative Governance in Education: A Social Psychology Approach to Enhancing School–Government Relations - Lin Ma; Mohd Mahzan Bin Awang; Anuar Bin Ahmad (Environment and Social Psychology, 2025)
Collective efficacy is the shared idea of a group of supposedly nonexistent individual abilities of the group to plan and execute actions required to achieve the preferred outcomes in a conjoint manner. This is a fundamental faith in the school and government administration: the schools and government agencies must not merely depend upon each other in respect of competence, they must also believe themselves to be in a competent relationship. These partnerships however are not successful because most of them lack the same sense of capability to achieve the objectives that they want to achieve together. In a bid to overcome this challenge, this Article uses the Collective Efficacy Theory by Albert Bandura as a framework to comprehend and enhance school-government relations. The article is a theoretical and empirical effort to deepen collaborative governance in terms of the notion of collective efficacy. On the qualitative illustrations that are used in the cases that are reported in the educational reforms, on the policy documentation and analysis of the institutional practice, we are searching four dimensions, which bring about an integrated effect on the government: mutual trust, procedural justice, shared identity, and jointly resolving the issues. We are, in conjunction with decision makers and school leaders, creating a section on clinical, and this may be utilized to build further trust on mutual skills and scale interventions. These findings, combined with the connotations of theory building that entail collective impacts within the gist of management analysis, give rise to some implication on how the governments and schools can transcend over the hierarchical / undesired interrelationships to emerge with the actual partnership that results in high levels of effective policy execution and learning outcomes.